DETERMINAN VOLUME EKSPOR SISA LOGAM MULIA INDONESIA KE JEPANG TAHUN 1996-2021 - Anjani, Ni Komang Tri; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025DO - 10.24843/EEB.2025.v14.i03.p12, 2025)
Indonesia has several leading export commodities divided into the oil and gas and non-oil and gas sectors. Based on data from the Ministry of Industry (2020), precious metal commodities experienced the largest increase in export value in 2020, precisely in the first quarter of 90.6 percent. From the derivatives of precious metal commodities, HS code 7112 or precious metal scraps are a large commodity exported by Indonesia to Japan. The purpose of this study was to see the relationship between the bilateral cooperation variables IJEPA (Indonesia-Japan Economic Partnership Agreement), the Rupiah exchange rate and Japanese economic growth on the volume of precious metal scrap exports in 1996-2021. The results of this study are that IJEPA has a significant positive effect, the exchange rate has a significant negative effect, while Japan GDP (Gross Domestic Product) does not have a significant effect on the volume of Indonesia's precious metal scrap exports to Japan in 1996-2021. The implication of this study is that the government is expected to be able to make greater use of bilateral and multilateral economic cooperation with the aim of increasing exports of leading commodities in Indonesia so that it can support the Indonesian economy.